Kabul Carnival : Gender Politics in Postwar Afghanistan - Billaud, Julie (Book collections on Project MUSE., 2015)
Offering one of the first long-term on-the-ground ethnographies of Afghanistan since the arrival of allied forces in 2001, Kabul Carnival explores the contradictions, ambiguities, and unintended effects of the emancipatory projects designed for Afghan women and imposed by the international community.